(untitled) (American Journal of Youth and Women Empowerment, 2023)
This study determined the status of crime victims, particularly victims of violence against women in order to arrive in practical solutions to the stated problems of the study. Specifically, it sought to determine the factors contributory to victimization among crime victims, the effects of victimization, the support extended for the treatment of crime victims, in order to arrive in recommendations to assist crime victims and minimize the impact of victimization. It made use of the descriptive-qualitative method of research. The researcher found out that the primary factors that lead to the victimization of women victims of violence are socioeconomic factors. Most of the abuses committed to victims were in the form of verbal abuse so there is no much visible physical effect. There is lack of support given to the victims. In terms of suggestions made by the victims to help other victims, most of them suggested livelihood programs because they believe that some cases of violence against women stem from financial reasons.